Pengaruh Kombinasi Takaran Bokashi Kotoran Burung Puyuh dan Pupuk NPK 16:16:16 Terhadap Pertumbuhan dan Hasil Tanaman Kacang Hijau (Vigna radiata L.) - Maulana, Mego Syef; Bustari Badal; Dewirman Prima Putra (Jurnal Research Ilmu Pertanian, 2022)
Research on the effect of the combination of quail droppings bokashi + NPK 16:16:16 on the growth and yield of green beans (Vigna radiata L.) was carried out in Koto Panjang Ikur Koto Village, Koto Tangah District, Padang. This research was started from December 2019 to March 2020. The purpose of this study was to obtain the best combination of quail droppings + NPK 16:16:16 for growth and yield of green bean plants. This study used a randomized block design with 9 treatments and 3 groups. The treatments were given with the dose of bokashi quail manure with a combination of NPK fertilizer 16:16:16, namely A = 0 ton / ha + 100 kg / ha NPK; B = 5 tonnes / ha + 50 kg / ha NPK; C = 5 tonnes / ha + 100 kg / ha NPK; D = 10 tonnes / ha + 50 kg / ha NPK; E = 10 tonnes / ha + 100 kg / ha NPK; F = 15 tonnes / ha + 50 kg / ha NPK; G = 15 tonnes / ha + 100 kg / ha NPK; H = 20 tonnes / ha + 50 kg / ha NPK; I = 20 tonnes / ha + 100 kg / ha NPK. The results showed that the combination of quail dung bokashi + NPK fertilizer 16:16:16 showed no significant effect on the observed variable number of primary branches and had a very significant effect on plant height, flowering age, first harvest age, number of pods planted, number of pods per plot, percentage of pithy per plot, dry weight of seeds per plot, and significant differences in seed dry weight per plant. The combination of quail droppings bokashi + NPK 16:16:16, namely 15 tonnes / ha + 50 kg / ha NPK is the best measure for the growth and yield of green bean plants.